2010
DOI: 10.1021/ac102146g
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Isotope Labeling for Profiling Carboxylic Acid-Containing Metabolites in Biofluids by Mass Spectrometry

Abstract: We have developed a new isotope labeling method, based on the use of isotope-coded p-dimethylaminophenacyl (DmPA) bromide as a reagent, combined with liquid chromatography-mass spectrometry (LC-MS) for high-performance metabolome analysis with a focus on profiling carboxylic acid-containing metabolites. Derivatization is simple, fast (1 h plus 30 min for quenching the reaction), and applicable to a wide range of carboxylic acids with a high yield and little or no side reaction products. This labeling method is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
164
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 174 publications
(168 citation statements)
references
References 18 publications
1
164
0
3
Order By: Relevance
“…CIL LC-MS has been shown to provide high accuracy and precision for metabolome profiling [1][2][3][4], which can be attributed to simultaneous measurement of the co-eluted analytes and their isotope counterparts to overcome ion suppression, instrument drift and other technical problems. Furthermore, chemical derivatization provides a useful means of improving the separation of polar or ionic metabolites in reversed phase (RP) LC as well as enhancing the ionization efficiency in electrospray ionization (ESI) by introducing a relatively hydrophobic and easily chargeable ESIactive tag [1,5,6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…CIL LC-MS has been shown to provide high accuracy and precision for metabolome profiling [1][2][3][4], which can be attributed to simultaneous measurement of the co-eluted analytes and their isotope counterparts to overcome ion suppression, instrument drift and other technical problems. Furthermore, chemical derivatization provides a useful means of improving the separation of polar or ionic metabolites in reversed phase (RP) LC as well as enhancing the ionization efficiency in electrospray ionization (ESI) by introducing a relatively hydrophobic and easily chargeable ESIactive tag [1,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…To date, several CIL reagents have been developed to quantify organic amines, carboxylic acids, carbonyl compounds and some other types of metabolites with varying degrees of performance [1,4,5,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. These research activities are mainly driven by the need of dealing with different classes of metabolites; a universally applicable derivatization reagent for LC-MS is not available at the present.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work, we have shown that CIL LC-MS using a rationally designed isotope labeling reagent could increase the metabolite detectability and quantification accuracy significantly for chemical-group-based submetabolome profiling2324. For example, 13 C-dansyl or 12 C-dansyl chloride could be used to differentially label amine- and phenol-containing metabolites for relative quantification of the amine/phenol submetabolomes with high coverage2325.…”
mentioning
confidence: 99%
“…CAs are predominantly analyzed using gas chromatography coupled to mass spectrometry (GC-MS) after their chemical derivatization with reagents such as boron trifluoride / butanol [184], hexamethyldisilazane [185], N-methyl-N-tertbutyldimethylsilyltrifluoroacetamide [186] or N-methyl-N-trimethylsilyltrifluoroacetamide [187,188]. Another common technique for analysis of organic CAs is anion exchange chromatography [189] or ion exclusion chromatography [190] coupled to mass spectrometry.…”
Section: Methods For Carboxylic Acid Analysismentioning
confidence: 99%